Search for the Associated Production of a b Quark and a Neutral Supersymmetric Higgs Boson that Decays into tau Pairs - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Wang, M. H. L. S.; et al. (Amer Physical Soc, 2010)
We report results from a search for production of a neutral Higgs boson in association with a b quark. We search for Higgs decays to tau pairs with one tau subsequently decaying to a muon and the other to hadrons. The data correspond to 2: 7 fb(-1) of p (p) over bar collisions recorded by the D0 detector at.. root s = 1.96 TeV. The data are found to be consistent with background predictions. The result allows us to exclude a significant region of parameter space of the minimal supersymmetric model.